A participatory intervention to improve the mental health of widows of injecting drug users in north-east India as a strategy for HIV prevention - Chandra Prabha; Kermode Michelle; Devine Alexandra; Herrman Helen (BMC, 2007)
Abstract Background Manipur and Nagaland, in the north-east of India, are classified as high prevalence states for HIV, and intravenous drug use is an important route of transmission. Most injecting drug users (IDUs) are men, an estimated 40% are married, and death rates have been high in the last five years, consequently the number of widows of IDUs has increased. Many of these widows and their children are HIV-infected and experience poor health, discrimination, and impoverishment; all factors likely to be compromising their mental health. People with poor mental health are more likely to engage in HIV risk behaviours. Mental health can be promoted by public health actions with vulnerable population groups. Methods We designed an intervention study to assess the feasibility and impact of a participatory action process to promote the mental health and well-being of widows of IDUs in Manipur and Nagaland, as a strategy for reducing the risk of engagement in HIV risk behaviours. This paper describes the background and rationale for the study, the intervention, and the study methods in detail. Results Pending analysis. Conclusion This intervention study will make a significant contribution to the emerging evidence that supports associations between mental health and HIV. The concept of promoting mental health among women who are vulnerable to HIV infection or already infected as a strategy for HIV prevention in a development setting is breaking new ground.